Analisis Biomekanik Teknik Smash Sepak Takraw Menggunakan Analisis Gerak Berbasis Video - Dadang Budi Hermawan; Muhammad Agreindra Helmaiwan; Yanyan Sofiyan (Indonesian Journal of Physical Education and Sport Science, 2026)
Study Purpose. The smash technique is one of the most important offensive skills in sepak takraw and plays a decisive role in scoring points. Effective smash execution requires optimal coordination of the lower limbs and trunk, which can be examined through biomechanical analysis. This study aimed to analyse the biomechanical characteristics of the sepak takraw smash technique using video-based motion analysis. Material and Methods. This study employed a descriptive quantitative research design. The participants were 15 male students from the Physical Education, Health, and Recreation (PJKR) study program, aged 18–22 years, who actively participated in sepak takraw training. Smash movements were recorded with a smartphone camera that supports slow motion. Video-based motion analysis software was used to measure biomechanical variables, including knee, hip, and ankle joint angles; kicking-leg swing velocity; ball contact height; and trunk inclination angle. Descriptive statistics were used to calculate means and standard deviations for each variable. Result. The results showed that participants performed the smash technique with a mean knee angle of 158.4° ± 5.2° and a hip angle of 142.1° ± 6.3° at the moment of ball contact. The kicking-leg swing velocity reached an average of 18.6 ± 2.4 m/s, while the ball contact height was recorded at a mean of 2.15 ± 0.12 meters. Additionally, the trunk inclination angle showed an average of 12.5° ± 3.1°, demonstrating a forward body posture that contributes to balance. Conclusion. Video-based motion analysis is an effective and practical method for evaluating the biomechanical characteristics of the sepak takraw smash technique. The findings provide useful information for coaches to improve smash performance and develop training programs based on biomechanical principles.